Equações no ensino médio: uma metanálise qualitativa das dissertações e teses produzidas no Brasil de 1998 a 2006 - Nagamachi, Marcos Toshio (2009)
The present study is a synthesis of Brazilian researches which focus on equations in high school. The analysis material constituted of six dissertations published on the Mathematics Education from 1998 to 2006. The essays were were selected according to some pre-defined research instruments and criteria. The methodology characterizes itself as a documental study denominated qualitative meta-analysis which makes a systematic revision of searches set, aiming a synthesis of these productions. It is presented a study confront, more specifically of their objectives, theoretical and theoretical-methodological framework, and conclusions. The results confirm a preference for algebraic equations, a divergence in the choice of the theoretical framework and a necessity to conciliate algebra and geometry. The study indicate results that can offer subsidies to new researches, such as the lack of researches in some aspects on this theme